Relationship of size of corpus callosum with white matter changes in elderly population; A retrospective analytical cross-sectional study. (December 2022) - Shrestha, Sadina; Dhakal, Bishal; Sapkota, Sachin; Pathak, Bishnu Deep; Dhakal, Binaya; Mainali, Saugat; Lamicchane, Saurav; Simkhada, Nabin; Ale Magar, Priajan; Dawadi, Sagun; Phuyal, Subash
Abstract: Purpose: To study the relationship of size of corpus callosum with white matter changes in the elderly population. Materials and methods: This was a retrospective analytical cross-sectional study. The relationship between the corpus callosum and white matter changes was studied using the magnetic resonance imaging technique, where white matter changes were graded based on Fazekas grading. The Spearman rank order correlation was used to assess the relationship between the size of corpus callosum and white matter changes. Results: The whole corpus callosum (ρ = 0.165, p = 0.044) and rostrum (ρ = −0.232, p = 0.004) was significantly correlated with white matter changes based on Fazekas severity grading. Similarly, in bivariate regression analysis, white matter changes were strongly correlated with rostrum (standardized β-coefficient = -0.186, p = 0.023). While taking gender in sub-group analysis, white matter changes were significantly correlated with rostrum (ρ = -0.252, p = 0.021) and splenium (ρ = −0.229, p = 0.036) in male and with rostrum (ρ = −0.245, p = 0.048) only in female groups. Conclusions: Corpus callosum size is associated with white matter changes in the elderly population. This association can give insight into the neuropathology of diseases involving the central nervous system. Highlights: Corpus callosum is the prime fiber tract connecting left and right cerebral hemispheres. Thinning of corpus callosum and white matter loss have been shown to occur with aging. The MRI has been a vital tool in assessing the changes in brain with age. Corpus callosum size is associated with white matter changes in elderly population.